2020
DOI: 10.1111/avj.13037
|View full text |Cite
|
Sign up to set email alerts
|

Marking to weaning production aspects of lambs provided with NSAID analgesia compared with lambs receiving no analgesia at the time of elastrator ring marking

Abstract: The provision of analgesia at the time of marking has been adopted by the Australian sheep industry, but data on production benefits are lacking. In the current study, alternate lambs were provided with either meloxicam (non‐steroidal anti‐inflammatory drug [NSAID], n = 781) or no analgesia (NONE, n = 822) at the time of ring castration and tail docking. Six distinct management groups of lambs were studied. Lambs were weighed immediately before marking and then again at weaning. There was no significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Other production measures, such as survival rate are strong motivators to introduce pain mitigation strategies in livestock practice. The use of NSAIDs after castration and tail docking in lambs significantly improved lamb survival between marking and weaning in one study ( Small et al, 2020 ). Other studies investigating lamb mortality following marking with or without analgesia have failed to find a significant difference in survival.…”
Section: Measuring Pain In Livestockmentioning
confidence: 99%
See 2 more Smart Citations
“…Other production measures, such as survival rate are strong motivators to introduce pain mitigation strategies in livestock practice. The use of NSAIDs after castration and tail docking in lambs significantly improved lamb survival between marking and weaning in one study ( Small et al, 2020 ). Other studies investigating lamb mortality following marking with or without analgesia have failed to find a significant difference in survival.…”
Section: Measuring Pain In Livestockmentioning
confidence: 99%
“…When animals are in persistent negative affective states and/or pain their feed intake usually decreases leading to a loss in body weight. The evidence for weight loss or reduced growth following husbandry procedures performed without analgesia is equivocal ( Small et al, 2020 ; Stock et al, 2021 ). Bates et al (2015) demonstrated improved milk consumption and average daily weight gain over 15 days in dairy calves that were disbudded by farmers and given NSAIDs as analgesia opposed to calves that were not given NSAIDs.…”
Section: Measuring Pain In Livestockmentioning
confidence: 99%
See 1 more Smart Citation
“…While multimodal analgesia is currently recognised as best practice for lambs undergoing lamb marking in Australia [1], of the three studies that used multimodal analgesia, [26,32,91] only the combinations of Tri-Solfen ® with meloxicam and lignocaine and meloxicam are registered for use in sheep (see Table 1). The combination of meloxicam and Tri-Solfen ® provided some level of analgesia in most studies [23,24,33].…”
Section: Nsaidsmentioning
confidence: 99%
“…Non-steroidal anti-inflammatories (NSAID) have also been shown to reduce some pain behaviours and physiological signs of pain following castration and tail docking [ 63 , 64 ]. Small et al [ 65 ] found significantly lower lamb mortality from marking to weaning in ring-docked and castrated lambs treated with the NSAID meloxicam compared to those that received no form of analgesia. This study did not have a handled control group, and the causes of lamb mortality were not recorded, which limits the conclusions that can be drawn.…”
Section: Tail Docking and Castration—science And Policymentioning
confidence: 99%